Land administration service delivery and its challenges in Nigeria: A case study of eight states - Ghebru, Hosaena; Okumo, Austen (International Food Policy Research Institute, 2017)
This paper assesses the nature of land administration service delivery in Nigeria using data collected from three sets of participants in land administration processes: 76 service providers, 253 beneficiaries, and 172 professionals. The data were collected from eight states selected from the six geopolitical zones of the country—Cross River, Benue, Bauchi, Ekiti, Enugu, Kaduna, and Lagos states, plus the Federal Capital Territory (Abuja). These were chosen because they are considered to have advanced land administration systems. Our findings show that land registration processes in Nigeria take a long time: nearly 80 percent of beneficiaries and 41 percent of professionals responded that land registration took more than two years to complete after first apply-ing. This difference between beneficiaries and professionals may stem from the fact that many professionals, who gener-ally are better educated, may know more about the application process than do beneficiaries and are able to navigate the process more efficiently. Land registration information guidelines seem to be rarely available to the public. Consequently, the dominant means of access to land administration institutions is through direct contact. Coordination among govern-ance structures put in place by states for land administration also was found to be poor, especially in Bauchi and Enugu states, where very low levels of cooperation on issues related to land administration reforms were observed.